Composite Indicator of Financial Development in a Benefit‐of‐Doubt Approach. (20th June 2013) - GIAMBONA, FRANCESCA; VASSALLO, ERASMO
Abstract We use data by the World Economic Forum (WEF) to build a Composite Financial Development Index (CFDI) alternative to the WEF financial index. Unlike the WEF index, the CFDI optimally combines seven dimensions with non‐fixed weights determined endogenously without recourse to subjective opinions of experts. The CFDI is obtained by applying a Data Envelopment Analysis linear programming model with proportion restrictions on weights calculated in a Benefit‐of‐Doubt approach. In this way, the CFDI scores allow us to group 60 countries by different levels of financial development identifying dimensions that contribute to good or poor financial performances, taking into account the different characteristics of the financial systems in the countries under investigation.